Factors Influencing Mental Health Among Chinese Medical and Non-medical Students in the Early Stage of the COVID-19 Pandemic - Xiong, Peng; Ming, Wai-kit; Zhang, Caiyun; Bai, Jian; Luo, Chaohua; Cao, Wenyuan; Zhang, Fan; Tao, Qian (Frontiers in Public Health, 2021)
Background: The 2019 coronavirus disease (COVID-19) pandemic is a public health emergency of international concern. This study aims to assess the psychological outcomes and its influencing factors among university students during the COVID-19 pandemic in China. Methods: A cross-sectional online survey using structural questionnaires was conducted from 20 February to 20 March 2020. Psychological outcomes were assessed by the Depression, Anxiety and Stress Scale (DASS-21). Influencing factors were assessed by the COVID-19 knowledge, mindful coping scale and sense of control scale. Results: Our sample comprises of 563 university students (male = 172, mean age = 21.52). Among them, 382 are medical students. Among the participants, 12.26%, 18.47%, and 8.53% of them have moderate to severe level of depression, anxiety, and stress symptoms, respectively. Compared with the non-medical students, the medical students had a higher knowledge of COVID-19, a higher sense of awareness, and less mental health symptoms. After controlling the covariance, perceived constrains of sense of control was negatively associated with depression, anxiety, and stress among both medical and non-medical students. Negative emotions prevention of mindful coping was negatively associated with depression and anxiety among non-medical students. Conclusions: During the COVID-19 pandemic in China, mental health of university students was affected. Our findings suggested that sense of control is a protective factor for both medical and non-medical students while mindful coping is a protective factor for only non-medical students.